Influence of Online Reviews on Consumer Good Purchase Intent: Evidence from Vietnam - Cuong, Pham Hung (International Journal of Supply Chain Management, 2020)
Purpose of the study: The major transformation in the shopping process accelerated the ease and convenience of people but has left loopholes in filling the void of tangibility and assurance for the price paid. A remark from a previous customer or an expert is an absolute determinant in determining the validity of the goods and boosts its sale, online. The main purpose of the study is the find which type of reviews affect the consumer goods purchase intent. Originality and Value: This study portrays about the shift in the pattern of online shopping and stresses on factors that can help in entrusting confidence in customers who purchase consumer goods over the web. Vietnam is known as a growing economy that has embraced internet for constructive purposes. Research Design: The recent study is empirical in nature. It involves a sample size of 358 respondents that has been collected through a structured questionnaire. The data has been collected from the respondents on the basis of purposive sampling and has been analyzed with the help of mean score and multiple regression.  Findings: It was found from the study that the most important aspects of online reviews are they give hidden information about product features and usage these are the first thing that one refers before making products Extended reviews give through information about the product and more helpful. Most of the forms of online reviews have the positive impact on purchase intent. However, purchase intent is not affected by – I always believe in online reviews and online reviews are biased.